2020
DOI: 10.3991/ijim.v14i11.11358
|View full text |Cite
|
Sign up to set email alerts
|

E-Commerce Competence Assessment Mobile Application Development for SMEs in Thailand

Abstract: The objectives of this study are to develop e-Commerce self-assessment application based on research and to evaluate the adoption of the system by using the Technology Acceptance Model (TAM) which are designed for SMEs self-assessment and the government agencies are able to retrieve the report. The system development deployed Microsoft .NET CORE Technology with C# language, HTML/CSS/JS for Mobile Web Development. All data will store on Aurora RDS. The web deployed on Amazon public cloud that will autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(39 reference statements)
1
9
0
1
Order By: Relevance
“…Penelitian ini menggunakan model Research and Development Borg and Gall yang telah dimodifikasi menjadi delapan langkah untuk mempersingkat waktu dan keadaan lapangan (Z. Arifin, 2011;Limpeeticharoenchot et al, 2020;Wongkhamdi et al, 2020). Selain itu, peneliti juga merasa bahwa tujuan penelitian yaitu untuk menghasilkan produk, mengetahui kelayakan produk, dan menguji keefektifan produk dalam meningkatkan kualitas pelayanan adminitrasi keuangan.…”
Section: Metode Gambar 1 Langkah-langkah Penelitianunclassified
“…Penelitian ini menggunakan model Research and Development Borg and Gall yang telah dimodifikasi menjadi delapan langkah untuk mempersingkat waktu dan keadaan lapangan (Z. Arifin, 2011;Limpeeticharoenchot et al, 2020;Wongkhamdi et al, 2020). Selain itu, peneliti juga merasa bahwa tujuan penelitian yaitu untuk menghasilkan produk, mengetahui kelayakan produk, dan menguji keefektifan produk dalam meningkatkan kualitas pelayanan adminitrasi keuangan.…”
Section: Metode Gambar 1 Langkah-langkah Penelitianunclassified
“…Some of these mobile applications has even the GPS capability to track distance and speed of the user (i.e., while bike riding or running) [7]. However, upon conducting a systematic review, most previously developed mobile fitness application were found to be lacking on beginner exercise as highlighted in the previous sub section [1], [5], [7], [8], [11], [18], [19]. The frequency usage of mobile fitness application among beginner users is very low [20], [21].…”
Section: Related Literaturementioning
confidence: 99%
“…Future exercise technique will need to progress at a steady pace and not push a person too hard so that the exercise experience remains pleasant. Further, the systematic review also found most developed mobile fitness application was the form of one size fits all, thus limiting the benefits to beginner users [1], [19], [23]. Based on this systematic review it can be argued that the usage of previously developed mobile fitness application has not been fully adopted and utilize especially among the beginner users [1], [10].…”
Section: Related Literaturementioning
confidence: 99%
“…We conducted a cluster analysis for building the BDMM through LCA by using the Proc LCA software [49] and R package v.1.4.1 [50]. The number of groups that were tested ranged from three to six, as BDMMs, in general, comprise four-six groups [34].…”
Section: Questionnaire and Validationmentioning
confidence: 99%